1989
DOI: 10.1111/j.1471-4159.1989.tb02550.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Brain Glutathione by l‐Buthionine Sulfoximine Potentiates the Dopamine‐Depleting Action of 6‐Hydroxydopamine in Rat Striatum

Abstract: Sprague-Dawley rats were anesthetized with chloral hydrate, and plastic cannulae were permanently implanted into the lateral ventricles. The animals then were allowed to recover for 1-2 days. L-Buthionine sulfoximine (L-BSO), a selective inhibitor of glutathione (GSH) synthesis, and 6-hydroxydopamine (6-OH-DA), a selective catecholaminergic neurotoxin, were administered intracerebroventricularly. The striatal concentrations of GSH and monoamines were determined by HPLC with electrochemical detection. Two injec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(44 citation statements)
references
References 14 publications
0
44
0
Order By: Relevance
“…Glutathione (GSH), responsible for detoxification of reactive oxygen and other radical species, is consistently decreased in cerebrospinal fluid of drug-naïve schizophrenia patients (Do et al, 2000), as well as in postmortem tissue (Yao et al, 2006). Polymorphisms in genes coding for enzymes that participate in GSH synthesis have been linked to schizophrenia risk (Tosic et al, 2006;Gysin et al, 2007), and acute frontal-brain GSH depletion in adult rodents was recently shown to produce disruptions in short-term memory, supporting the link between depletion of brain GSH levels and cognitive impairments that occur in schizophrenia (Pileblad et al, 1989;Jacobsen et al, 2005;Dean et al, 2009). Moreover, acute GSH depletion potentiates the release of dopamine produced by amphetamine in striatum and potentiates the behavioral effects of NMDA-R antagonists as a well as those of amphetamine (Jacobsen et al, 2005).…”
Section: The Role Of Superoxide In the Persistent Effects Of Nmda-r Amentioning
confidence: 86%
“…Glutathione (GSH), responsible for detoxification of reactive oxygen and other radical species, is consistently decreased in cerebrospinal fluid of drug-naïve schizophrenia patients (Do et al, 2000), as well as in postmortem tissue (Yao et al, 2006). Polymorphisms in genes coding for enzymes that participate in GSH synthesis have been linked to schizophrenia risk (Tosic et al, 2006;Gysin et al, 2007), and acute frontal-brain GSH depletion in adult rodents was recently shown to produce disruptions in short-term memory, supporting the link between depletion of brain GSH levels and cognitive impairments that occur in schizophrenia (Pileblad et al, 1989;Jacobsen et al, 2005;Dean et al, 2009). Moreover, acute GSH depletion potentiates the release of dopamine produced by amphetamine in striatum and potentiates the behavioral effects of NMDA-R antagonists as a well as those of amphetamine (Jacobsen et al, 2005).…”
Section: The Role Of Superoxide In the Persistent Effects Of Nmda-r Amentioning
confidence: 86%
“…PD models have received special attention since a severe GSH depletion in the substantia nigra of PD patients has been described (2-4). Experimental GSH depletion does not cause nigral degeneration by itself in the rat, but it renders DA neurons more susceptible to subsequent insults (18,19,24). In cell culture models, different tolerances to GSH depletion have been reported depending on cell type and the brain region used for primary cultures.…”
Section: Discussionmentioning
confidence: 99%
“…However, the reduction of GSH levels may rather enhance the susceptibility of DA cells to the toxicity of other insults, promoting the neurodegenerative process. For example, GSH depletion induced by L-buthionine-(S,R)-sulfoximine (BSO) treatment, a selective GSH synthesis inhibitor (23), enhances the susceptibility of DA neurons to the toxicity of the mitochondrial complex I inhibitor MPTP/MPP ϩ in vivo (18) and in vitro (20), potentiates the toxicity of 6-hydroxydopamine (6-OHDA) in rat striatum (24), and even changes the DA cell-specific trophic effect of NO in midbrain cultures into one that is neurotoxic (25).…”
mentioning
confidence: 99%
“…The SN generally contains lower GSH levels than the cortex, cerebellum, hippocampus, or striatum (123) and is therefore considered to be a target of oxidative stress. Decreasing GSH levels in dopaminergic neurons by BSO potentiates susceptibility to some dopaminergic neurotoxins such as 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP), 1-methyl-4-phenylprydinium (MPP + ), and 6-hydroxydopamine (124,125). Loss-of-function of GCLM also enhanced dopaminergic neurotoxicity, while GCLM overexpression rescued the neuronal loss in flies overexpressing α-synuclein, a principle component of Lewy bodies that define PD pathologically (126).…”
Section: Parkinson's Model and Eaac1mentioning
confidence: 99%